Emergence Time and Sequence of Primary Teeth in a Sample of Nepalese Children - Upadhyay, S.; Deoju, R.; Mahanta, S. K.; Shrestha, R. (Kathmandu University Medical Journal, 2022)
Background Primary teeth emergence is an important milestone in children and timing of emergence varies among populations.Objective To determine the emergence time and sequence of primary teeth in a sample of Nepalese children visiting Dhulikhel Hospital.Method A descriptive cross-sectional study was conducted in children of 5 months to 4 years visiting Dhulikhel Hospital. The emergence of incisal tip to incisal margin for incisors and canines, cusp tip to occlusal margin of molars visible were recorded along with age in months and gender. Descriptive statistics was done to calculate the mean age of emergence of each tooth with standard deviation. Unpaired t-test was used to assess the difference between the mean age of emergence of teeth between right and left sides and between boys and girls.Result The first teeth to emerge was mandibular central incisor at the age of 9.37 ± 1.42 months and the last one was maxillary second molar at the age of 32.91 ± 6.39 months. There was no significant difference in the mean emergence time between the maxillary and mandibular jaws, between right and left sides of jaws and between boys and girls except for primary maxillary right central incisor and mandibular right second molar which was found to be emerged early in girls.Conclusion The emergence time and sequence of primary teeth observed in the present study can be used as a baseline data for the children of Kavre district.